Pengaruh Peningkatan Computational Thinking Siswa Kelas 5 Melalui Pembelajaran Dasar Coding - Tuhfah Humaira Mufidah; Majid , Nuur Wachid Abdul (Buletin Literasi Budaya Sekolah, 2024)
The digital era is a challenge in human adjustment and development, especially in the world of education. Students are required to master innovative values through creative thinking, develop innovative products and services, and adopt an innovative thinking perspective, commonly known as Computational Thinking. This research was conducted at SD Negeri Cimanggu Kecil, Central Bogor, highlighting the lack of engagement and customization of students' needs in computer learning. The author implemented the Computational Thinking approach with an introduction to basic programming using the Scratch website for 3 days of meetings. In the research, using quantitative methods with a quasiexperiment research design with the type of The Nonequivalent Control Group Design. The data tested came from student learning outcomes on the pre-test and post-test of the Class AKM from the Experiment Class and Control Class to see the effect of effectiveness on the development of Computational Thinking from the results of the N-gain test in percentage it was known that the effect of effectiveness on literacy and numeracy was in the ineffective category because the N-gain < 40% where the variables had been tested independent sample t test for the results of both homogeneous.